Transformational Leadership of School Principals in the Administrative Management of Elementary Schools and Its Impact on School Performance - Saprialman, Saprialman; Fauziyah, Syifa (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
Effective school administration is an important factor in supporting overall school performance. However, there are still various administrative problems that are bureaucratic, inflexible, and not optimal in supporting the achievement of institutional goals. These conditions require the leadership of school principals who are capable of making strategic and sustainable changes. This study aims to analyze the transformational leadership of school principals in school administration and its impact on school performance. This study uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observations, and documentation studies involving school principals, administrative staff, and teachers. Data analysis was carried out systematically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the transformational leadership of school principals encourages changes in administrative governance that are more participatory, transparent, and service-oriented. The principal acts as a driver of change by building a shared vision, providing motivation, and optimizing school resources. Administrative governance based on transformational leadership has a positive impact on improving school performance, especially in the effectiveness of administrative services and support for the learning process. This study concludes that the transformational leadership of the principal contributes significantly to strengthening administrative governance and improving school performance in a sustainable manner.